ANCA-Associated Vasculitis With Anti-GBM Disease and Two Types of Tumors: A Case Report - Li, Xiuxiu; Huang, Meichun; Liu, Jun (Frontiers in Medicine, 2022)
Abstract Introduction: Anti-neutrophil cytoplasm antibody (ANCA)-associated-vasculitis and anti-glomerular basement membrane (GBM) disease are types of autoimmune diseases that are characterized by the presence of circulating autoantibodies. Most patients with these diseases experience sudden onset, rapid progress, and poor prognosis. The purpose of the present article is to report a case of ANCA-associated vasculitis with anti-GBM disease and two types of tumors. Case Report: A 63-year-old Chinese woman who underwent resection for rectal cancer 6 years before and for lung adenocarcinoma 4 years before, presented with fever and nasal obstruction, for the past 2 months and chondritis of an ear for the past 1 month. The patient failed to respond to an anti-infection treatment at local and higher-level hospitals with the first episode of “recurrent sinusitis and fever”. Later, systemic symptoms such as fatigue, numbness of the limbs, and auricular chondritis gradually aggravated, followed by an increase in inconspicuous hematuria, proteinuria, and serum creatinine level. After admission, the GBM antibody, C-ANCA, and PR3 were positive. The renal puncture was diagnosed as anti-glomerular basement membrane antibody disease. After treatment, her serum creatinine decreased to 104 umol/l. Discussion: In the present report, we introduced the case of a rare double-positive disease in a patient with two types of tumors. Importantly, we noted that colon cancer and lung cancer, PR3, and anti-GBM disease may be related to their pathogenesis and manifestations. Further research is warranted to confirm these hypotheses.